Not Every Wheeze is Asthmatic: An Aspiration Pneumonia Case Report - Silva, Gabriel Melo Alexandre; Fonseca, Herbert Iago Feitosa; Souza, Pablo André Brito de; Oliveira, Ana Cássia Silva; Nobrega, Luciana Lopes Albuquerque da (Archives of Clinical and Medical Case Reports, 2021)
Introduction: Wheezing in infants is an extremely common complaint, being markedly frequent in emergency services. Nonetheless, such a complaint is part of a wide spectrum of pathologies thus, demanding deeper investigation over the differential diagnosis must be addressed in an appropriate manner, in order to implement the necessary therapy as early as possible, and excessive intervention avoided, as much as possible Therefore, this case-report seeks to serve as a reminder of the importance of keeping a high suspicion on aspiration pneumonia even in previously healthy patients. The Case: HPDJ, male, date of birth (Dec, 30th of 2019), then 10 months and 10 days old, enters the medical emergency service of the pediatric hospital on November, 10th of 2020, with a report of flu-like symptoms that persisted for 10 days. The possibilities of bronchiolitis, pneumonia and SARS-COV 2 are questioned given the pandemic context, therefore being approached with salbutamol and prednisolone, chest x-ray and complementary exams. The patient is hospitalized, under regimen of ceftriaxone, salbutamol and general symptomatic medication. The patient is discharged 6 days after the first hospitalization with recovered general condition and without adventitious sounds or pathological findings on auscultation, being referred to the pulmonology outpatient clinic of the pediatric hospital. During outpatient follow-up, the patient complains of a feverish respiratory condition, and then the possibility of aspiration by a foreign body was questioned. On Dec, 09th, foreign body is removed, with subsequent improvement of symptoms in 48 hours. Conclusion: The maintenance of high clinical suspicion and attention to anamnesis are extremely important factors for the early diagnosis of less common causes of common complaints, such as aspiration of a